(3x^2-1)/(x+1)e^(2/x)-3x 当x趋于无穷时的极限
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/07 20:27:54
(3x^2-1)/(x+1)e^(2/x)-3x当x趋于无穷时的极限(3x^2-1)/(x+1)e^(2/x)-3x当x趋于无穷时的极限(3x^2-1)/(x+1)e^(2/x)-3x当x趋于无穷时的
(3x^2-1)/(x+1)e^(2/x)-3x 当x趋于无穷时的极限
(3x^2-1)/(x+1)e^(2/x)-3x 当x趋于无穷时的极限
(3x^2-1)/(x+1)e^(2/x)-3x 当x趋于无穷时的极限
lim(x→∞)[(3x²-1)e^(2/x)/(x+1)]-3x
=lim(x→∞)[(3x²-1)e^(2/x)-3x²-3x]/(x+1)
=lim(x→∞)[3x²[e^(2/x)-1]-3x-e^(2/x)]/(x+1)
=lim(x→∞){3x[e^(2/x)-1]-3-[e^(2/x)]/x}/(1+1/x)
=lim(x→∞){3x·2/x-3-[e^(2/x)]/x}/(1+1/x)
=lim(x→∞){6-3-[e^(2/x)]/x}/(1+1/x)
=3
答案:3
考虑其导数的极限。上下同除以x²得:lim x->∞ [(x+1)e^(2/x)-3x]/(3x²-1)=limx->∞ [(1/x+1/x²)*(e^(2/x)) -3/x] /(3-1/x²) =((0+0)*1 -0)/(3-0)=0
所以原式极限=∞
e^x+(x-3)e^x =[1+(x-3)]e^x =(x-2)e^x
关于极限1.lim((x^-1) + (x^-4))/((x^-2) - (x^-3)) x-> 正无穷2.lim ((e^x) - (e^-x))/((e^x) + (e^-x)) x-> 负无穷
求不定积分:∫(e^3x+e^x)dx/(e^4x-e^2x +1)
求不定积分f[(e^3x+e^x)/(e^4x-e^2x+1)]dx
∫ e^x-e^(-x)dx=e^x+e^(-x)|=e+1/e-2
(1-e^(x^2))/x
2e^(x-1),x
(X^2-X)E^(1-X)求导
lim x趋于0 (x(e^x+1)-2(e^x-1))/x^3
求极限lim(x~0)((e^x+e^2x+e^3x)/3)^1/xs
1/[(e^x+e^-x)^2]不定积分
∫ e^x/e^2x+1
求不定积分∫(e^3x-e^x)/(e^4x+3e^2+1)dx
求不定积分∫[(e^(3x)-1)/(e^(x)-1)]dx怎样得出∫[(e^(x)-1)(e^(2x)+e^(x)+1)/(e^(x)-1)]dx
∫(e^x+3x^2+(2/x)-1)dx
e^x/1+2e^2x不定积分,e^x/(1+2e^2x)
f(x)=x(e^x-1)-1/2 x
lim(x→0)e^x-x-1/x^2